Visceral adipose tissue and body fat mass: Predictive values for and role of gender in cardiometabolic risk among Turks - Onat, Altan; Ugur, Murat; Can, Guenay; Yuksel, Husniye; Hergenc, Guelay (ELSEVIER SCIENCE INC, 2010)
Objective: We investigated the predictive values of visceral adipose tissue area (VAT) and body fat mass for a composite endpoint consisting of type 2 diabetes and coronary heart disease and for incident metabolic syndrome Methods: We analyzed at 4-y follow-up 157 middle-aged men and women in whom body composition analyzer and single-scan computerized tomography had been used Results: Sex- and age-adjusted mean areas of visceral fat were 1 5-fold greater in individuals with than without the composite endpoint (P < 0 001). whereas abdominal subcutaneous fat was similar. Analysis of receiver operating characteristics tor the optimal criterion regarding the composite endpoint (in 37 participants) indicated a VAT of 130 cm(2) and accuracies of 60% in men and 85% in women Whereas age-adjusted VAT alone significantly predicted the composite endpoint in men. body fat mass or VAT predicted it in women (with 2 2- to 2 6-fold relative risks for 1-SD increment). Age-adjusted incident metabolic syndrome was significantly predicted by each parameter in men but only by fat mass in women Conclusion: Visceral adiposity in men and body fat mass in women seem to be of greater relevance in cardiometabolic risk for the prediction of which 130 cm(2) of VAT in both sexes and/or 27 kg of fat mass in women are useful cutoffs Sex differences may reflect the predominating role of visceral adiposity in men and of insulin resistance in women in this risk (C) 2010 Published by Elsevier Inc
Keywords: Coronary heart disease; Diabetes type 2; Metabolic syndrome; Obesity; Insulin resistance; Visceral adiposity; ABDOMINAL OBESITY; CARDIOVASCULAR-DISEASE; INSULIN-RESISTANCE; OLDER MEN; WOMEN; ASSOCIATION; POPULATION; DEFINITION; HEALTH; Nutrition & Dietetics